Introduction to Discrete Mathematics - Johnsonbagh, Richard (New Jersey, 2006)
This book is intended for a one- or two-term introductory course in discrete mathematics, based on my experience in teaching this course over many years. Formal mathematics prerequisites are minimal; calculus is not required. There are no computer science pre-requisites. The book includes examples, exercises, figures, tables, sections on problem-solving, sections containing problem-solving tips, section reviews, notes, chapter re-views, self-tests, and computer exercises to help the reader master introductory discrete mathematics. In addition, an Instructor's Guide and World Wide Web site are available.
Keywords: Discrete Mathematics